International law enforcement cooperation in the field of cybercrime (Academic Journal of Internal Affairs, 2018)
The essay provides an overview of the potential and institutional structure of international law enforcement cooperation in the field of cybercrime.
Keywords: cybercrime; cooperation; law enforcement